The toponymy of the villages in Ambon Island: A historical and archaeological study: Toponimi desa-desa di Nusa Ambon: Kajian sejarah dan arkeologi - Wijaya, Daya Negri; Deny Yudo Wahyudi; Umaroh, Siti Zainatul; Susanti, Ninie; Ertrisia, Rendy Aditya Putra (BRIN, 2021)
Previously, several toponymy studies have already been conducted both in the Nusa (Island) Ambon as well as in the City of Ambon. However, previous studies have not used the historical and archaeological approach. The use of this approach could ease the researchers to reveal the cross-cultural meeting in a specific locus. Taking the Island of Ambon as a locus, the researchers aim to find the origin of village names and the cultural intersection in Leihitu and Leitimor Peninsula. There were three steps conducted to collect and analyse data using historical and archaeological approach. Firstly, the researchers identified and took a tabulation of the village names, mentioned by the Hikayat Tanah Hitu (The Epic of Hitu Land) and three ancient maps. Secondly, the researchers identified various archaeological remains located in the scattered villages. Finally, the researchers analysed the origin of village names by searching the word-meanings, finding the present locations, and describing the role of the contemporary cultures (Islamic and Colonial period) in the past. The researchers found 12 villages with 22 archaeological remains. All related communities have the archaeological remains which could explain the local dynamics, but there are merely ten villages which name meanings could be identified.